Tweek atmospherics reflection height measurements due to geomagnetic storm observed in the low latitude region / Khairunnisa Zainal Ashar - Zainal Ashar, Khairunnisa (2012)
Tweek atmospherics are ELF/VLF pulse signals with frequency dispersion characteristics that originate from lightning discharge and propagate in the Earth-ionosphere waveguide mode over long distances. The Low latitude nighttime D-region ionosphere variations were analyzed using tweek atmospherics received at Selangor station, Malaysia (2.55°N, 101.46°E) during the 3 — 5 Aw-' 2010 geomagnetic storms. The storm occurred in th .cal nighttime had a maximum reading of geomagnetic index, Dst of -65 nT recorded by the World Data Centre (WDC). Tweek measurements during this period show a small increase of 94 km in the ionospherics VLF mean reflection heights compared to the 86 km on the magnetically quite day height prior to the magnetic storm days. Tweeks atmospherics was estimated coming from distances as far as 5232 km from the lightning source on the magnetic storm days.